MENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI METODE BERNYANYI PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS 1 - Aliffatul Inayah, Dian; Irwan Setyo Widodo; Yunus Tanthowi (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This classroom action research that has been carried out aims to improve the learning outcomes of first grade students at SDN Besuk 1, especially in the Pancasila Education subject through the singing method. This research is motivated by the lack of understanding of students regarding abstract materials such as symbols and values ​​of Pancasila. This research is a Classroom Action Research (CAR) which was carried out for two cycles involving 23 students. Data collection in this study was carried out in three ways, namely observation, learning outcome tests and documentation. The results obtained after carrying out the research showed that there was an increase in learning outcomes starting from 39% in the pre-cycle then to 52% in cycle I and then increasing to 82% in cycle II. Based on these data, it can be said that the singing method has proven effective in fostering concentration, increasing involvement, and understanding of students towards the material being studied. So the author suggests that the singing method can be used as an alternative as an appropriate initial strategy for learning in lower elementary school classes.